Pengaruh Likuiditas Dan Ukuran Perusahaan Terhadap Harga Saham - Bustanul Ulum (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2023)
This study has a purpose, namely to determine and analyze the effect of liquidity and company size on stock prices in primary consumption sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018 – 2020. This study uses a quantitative approach, this method uses the multiple linear regression analysis by doing classical assumption test, hypothesis test and coefficient of determination. The results of this study are obtained partially, liquidity has no effect on stock prices, firm size affects stock prices, while simultaneously liquidity and firm size affect stock prices.